Heart transplantation for pediatric foreign nationals in the United States. Issue 2 (11th January 2023) - Harano, Takashi; Sheth, Megha; Sasaki, Kazunari; Yu, Jeremy; Wightman, Sean C.; Atay, Scott M.; Sainathan, Sandeep; Kim, Anthony W.
Abstract: Background: This study aimed to clarify survival outcomes, waitlist mortality, and waitlist days of heart transplantation of pediatric foreign nationals compared to pediatric United States (US) citizens. Methods: We retrieved data from March 2012 to June 2021 in the United Network Organ Sharing (UNOS) registry. Results: Of 5857 pediatric patients newly waitlisted, 133 (2.27%) patients were non‐US citizen/non‐US residents (non‐citizen non‐resident [NCNR]). Patients with congenital heart disease were higher in the US citizen group than in the NCNR group (51.9% vs. 22.6%, p < .001); 76.7% of patients in the NCNR group (102/133) had cardiomyopathy. Of the 133 NCNRs, 111 patients (83.5%) underwent heart transplantation, which was significantly higher than that in the US citizen group (68.6%, p < .001). The median waitlist time was 71 days (IQR, 22–172 days) in the NCNR group and 74 days (29–184 days) in the US citizen group ( p = .48). Survival after heart transplant was significantly better in the NCNR group than in the US citizen group ( n = 3982; logrank test p = .015). Conclusions: Heart transplantation for pediatric foreign nationals was mostly indicated for cardiomyopathy, and their transplant rate was significantly higher than that in the US citizen group, with better survival outcomes. The better survival outcomes in the NCNR group compared to the US citizen group can likely be attributed to the differing diagnoses for which transplantation was performed.